Sputter deposition of ScAlN using large size alloy target with high Sc content and reduction of Sc content in deposited films. (9th June 2015) - Sumisaka, Masahiro; Yamazaki, Kenta; Fujii, Satoshi; Tang, Gongbin; Han, Tao; Suzuki, Yu; Otomo, Shohei; Omori, Tatsuya; Hashimoto, Ken-ya
Abstract: This paper describes deposition of ScAlN thin films by the conventional radio frequency (RF) magnetron sputtering using large size Sc–Al alloy targets with high Sc content. Two 4-in. Sc–Al alloy targets with the Sc content of 43 and 32% were prepared by the sintering method instead of the conventional dissolution method, and deposited film qualities and uniformity were evaluated. In both cases, uniform ScAlN thin films were obtained throughout the three inch wafer. However, measured Sc content was significantly lower than that of the target. Influence of the N2 content in the sputtering gas was also investigated, and the result indicated that nitridation of the target surface is at least one of the major reasons causing the reduction of the Sc content in the deposited films. We also reports variation in film qualities observed with the accumulated sputtering time.